2018
DOI: 10.1002/elan.201700815
|View full text |Cite
|
Sign up to set email alerts
|

Direct Electrochemical Nano‐immunosensor for Microcystin‐LR in Seawater

Abstract: Microcystins are potent hepatotoxins produced by cyanobacteria, which proliferate in wastewaters with high nutrient content. Due to their high toxicity and potential risk to human health, even at low concentrations, the development of a sensitive and rapid method for the monitoring of microcystin‐LR (MC‐LR) in water samples is of great importance. In this context, a new direct electrochemical nano‐immunosensor for MC‐LR detection using the liquid crystal (E)‐1‐decyl‐4‐[(4‐decyloxyphenyl)diazenyl]pyridinium bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
(75 reference statements)
1
3
0
Order By: Relevance
“…The limit of detection (LOD), calculated as three times the standard deviation of the intercept/slope, was 0.053 ng mL À 1 . Table 1 shows a brief comparison of the linear ranges and detection limits of the GCE/MGNnP-PEI-anti-MC-LR and other immunosensors for MC-LR detection, recently published in the literature [12,14,[16][17][18][32][33][34][35]. It can be observed that the LOD of the proposed immunosensor is close to that of previously reported LOD values.…”
Section: Analytical Performance Of Immunosensorsupporting
confidence: 70%
See 3 more Smart Citations
“…The limit of detection (LOD), calculated as three times the standard deviation of the intercept/slope, was 0.053 ng mL À 1 . Table 1 shows a brief comparison of the linear ranges and detection limits of the GCE/MGNnP-PEI-anti-MC-LR and other immunosensors for MC-LR detection, recently published in the literature [12,14,[16][17][18][32][33][34][35]. It can be observed that the LOD of the proposed immunosensor is close to that of previously reported LOD values.…”
Section: Analytical Performance Of Immunosensorsupporting
confidence: 70%
“…It was also found that the highest current suppression was obtained with an incubation time of 40 min, and thus this was considered the ideal time to incubate the MC‐LR antigen. In previous studies on electrochemical immunosensors used to detect MC‐LR, incubation times ranging from 10 to 240 min have been applied . The incubation time selected for the proposed immunosensor is therefore compatible with those cited in the literature.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations